2013
DOI: 10.1002/14651858.cd000122.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early light reduction for preventing retinopathy of prematurity in very low birth weight infants

Abstract: Early light reduction for preventing retinopathy of prematurity in very low birth weight infants (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…The previous LIGHT-ROP trial (Reynolds et al, 2002; Reynolds et al, 1998), conceived and run in the era when photic injury to the retina by military and medical equipment exposures was of great concern, was based on the premise that light was injurious to the retina. Limiting light exposure to the eyes of premature infants had no effect on the incidence and severity of ROP (Jorge et al, 2013; Phelps and Watts, 2000, 2001). However, a low, non-injurious level of light, rather than dark, is known to decrease the circulating current.…”
Section: Summary and Future Directionsmentioning
confidence: 92%
“…The previous LIGHT-ROP trial (Reynolds et al, 2002; Reynolds et al, 1998), conceived and run in the era when photic injury to the retina by military and medical equipment exposures was of great concern, was based on the premise that light was injurious to the retina. Limiting light exposure to the eyes of premature infants had no effect on the incidence and severity of ROP (Jorge et al, 2013; Phelps and Watts, 2000, 2001). However, a low, non-injurious level of light, rather than dark, is known to decrease the circulating current.…”
Section: Summary and Future Directionsmentioning
confidence: 92%
“…We hypothesized that when compared to infants receiving LCL, infants receiving ECL would gain weight faster, be discharged from the hospital earlier with lower costs, and have better sleep and neurodevelopmental (mental, motor, visual acuity) outcomes. Retinopathy of prematurity (ROP) and hearing outcomes were measured to insure safety; we hypothesized there would be no differences between the ECL and LCL interventions, based on previous evidence that reduced light exposure has no effect on ROP severity (Jorge, Jorge, & El Dib, ) or sensory development (Brandon et al, ).…”
mentioning
confidence: 99%
“…(140) There was no effect on ROP severity by reducing light. A subsequent Cochrane review also showed no effect on ROP from light exposure during the first 7 postnatal days (90). …”
Section: Current Clinical Trialsmentioning
confidence: 99%